Effectiveness of Scratch-based interactive learning media on students' mathematical problem-solving - Hidayatul Maqhfiroh; Hevy Risqi Maharani (Universitas Sarjanawiyata Tamansiswa, 2025)
Mathematical problem-solving ability is a fundamental skill essential for students’ academic success and real-world challenges. This study aims to design a Scratch-based educational game,